Family Support, Associated Factors, and Quality of Life Outcomes in Type 2 Diabetes: A Correlational Study - Adelia Karisma; Nila Kusumawati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Enhancing the quality of life of patients with diabetes is essential for maintaining effective diabetes management and improving long-term health outcomes. Family support is considered an important factor in achieving this goal. This study aimed to examine the relationship between family support and quality of life among patients with type 2 diabetes, including other associated factors. A quantitative study was conducted in Kampar Regency, Riau Province, Indonesia, from November 25 to December 6, 2025. A total of 141 outpatients with type 2 diabetes from a government hospital were selected using purposive sampling. Family support and quality of life were measured using the Hensarling Diabetes Family Support Scale (HDFSS) and Diabetes Quality of Life (DQoL) questionnaires. Data were analyzed using multiple linear regression. The results showed that the model explained 31.3% of the variance in quality of life (R² = 0.313, p < 0.001). Family support was significantly associated with quality of life (B = 0.447, 95% CI: 0.279–0.614, p < 0.001). Patients’ education level (B = 8.970, p = 0.003) and family education level (B = 11.108, p = 0.026) were also significant predictors. Other variables, including age, sex, occupation, income, marital status, duration of diabetes, complications, and family characteristics, were not significantly associated with quality of life (p > 0.05). These findings indicate that family support and educational background play important roles in improving the quality of life of individuals with type 2 diabetes. Therefore, interventions that strengthen family support and educational programs should be prioritized.